Automated ultrasonographic pupillary assessment: a new neuro-ophthalmological assessment tool - Weiting Chen; Min Tang; Yaling Jin; Lihui Chen; Jiuzhou Lin; Xuelin Yang (Journal of International Medical Research)
Objective To evaluate correlations between ultrasonographic pupillary assessment (UPA) and automated UPA in neurocritical patients. Methods This was a prospective, observational study of 20 adult patients admitted to the intensive care unit with neurological pathology. Between UPA and automated UPA, 40 pupillary measurements were made. The time required to conduct UPA and automated UPA on a single patient was consistently < 3 minutes. Automated UPA required a markedly shorter operational time than UPA. Results There were strong positive associations between UPA and automated UPA measurements, with the following correlations: right eye at rest, r  = 0.9973; left eye at rest, r  = 0.9989; right eye post-pupillary light response, r  = 0.9975; left eye post-pupillary light response, r  = 0.9955. Bland–Altman analyses confirmed the strong agreement between the two methods under both conditions, with most measurements falling within the limits of agreement. Both the right and left pupillary diameters at rest demonstrated consistency, and the post-pupillary light response measurements for both eyes indicated good agreement, with a few outliers. Conclusions Automated UPA was strongly correlated with UPA in neurocritical patients. Automated UPA is a rapid, feasible, and noninvasive method that enables the precise evaluation of pupillary size and light response.